News from Spain. News bulletin publ. by the Executive committee of the Spanish socialist labour party. (P.S.O.E./Partido socialista obrero español) Information and documentation office. . U.G.T. information(s). Information and documentation office of the General union of spanish workers (U.G.T./Union general de trabajadores de España)
French ed.: Nouvelles d'Espagne. Bulletin ...(ZK 32183). - Also titled: U.G.T. information(s). Information and documentation office of the General union of spanish workers (U.G.T./Union general de trbajadores de España)>